Transformasi Konsep Kebendaan dalam Era Digital: Dekonstruksi Status Hukum Aset Kripto sebagai Objek Perdata Modern di Indonesia - Lahay, Nadela Ramadhanty Caesarani; Nur Mohamad Kasim; Sri Nanang Meiske Kamba (Cattleya Darmaya Fortuna, 2025)
The rapid advancement of digital technology has given rise to cryptocurrency as a new economic instrument that challenges the traditional concepts of property under Indonesian civil law. This study analyzes the legal status of cryptocurrency assets within the Indonesian civil law system and the urgency of transforming the concept of property to accommodate modern digital realities. The main issue discussed is the ambiguity surrounding the status of cryptocurrency assets as legal objects under the Civil Code (KUHPerdata), which still primarily focuses on tangible physical objects, thereby creating a legal void in protecting property rights and digital asset transactions. This research employs a normative legal method with an analytical approach to examine legislation, legal doctrines, and comparative studies of international regulations. The findings indicate that although cryptocurrencies have been recognized as commodities through regulations by Bappebti and OJK oversight under the P2SK Law, their legal status as civil objects remains ambiguous because the Civil Code has yet to accommodate intangible digital objects with economic value. The study identifies the transformation of the property concept through the deconstruction of the physical existence requirement as an urgent need to ensure legal certainty and adequate protection for cryptocurrency users. The research recommendations include expanding the definition of